Individualized correction of sex steroid deficiency in early postmenopausal women with uterine leiomyoma - M. V. Koval; T. A. Oboskalova (Акушерство, гинекология и репродукция)
Aim: to develop individualized options for correcting sex steroid deficiency in early postmenopausal patients with uterine leiomyoma.Materials and Methods. 180 postmenopausal patients with uterine leiomyoma were examined. To correct menopausal manifestations, patients were prescribed: Group 1 (n = 60) – low-dose drug estradiol 1 mg/drospirenone 2 mg, Group 2 (n = 60) – ultra-low-dose drug estradiol 0.5 mg/drospirenone 0.25 mg, Group 3 (n = 60) – patients refused to take menopausal hormone therapy (MHT). Clinical and anamnestic, laboratory and instrumental examination was carried out by assessing vasomotor and genitourinary symptoms. Special attention was paid to ultrasound examination of the pelvic organs with Dopplerometry of the intratumoral vessels.Results. The vasomotor manifestations of menopausal syndrome in postmenopausal patients with uterine leiomyoma were effectively relieved with drug containing 17β-estradiol/drospirenone, regardless of component dosage (RR = 0.25). The size of nodes in uterine leiomyoma type 2–6 according to classification of The International Federation of Obstetricians and Gynecologists (FIGO) as well as Dopplerometry data in the uterine artery in postmenopausal women showed no changes after 9-month use of 17β-estradiol/drospirenone. In Group 1, increased vascularization intensity (RR = 1.4) and decreased peripheral vascular resistance in intranodular vessels were revealed in 6 % patients.Conclusion. The use of MHT drugs at varying component doses did not enlarge size of leiomyoma nodes nor affected hemodynamic parameters in the uterine arteries during 6-month-treatment. However, while prolonging MHT duration, it increased vascularization of myoma nodes assessed by measuring intranodular blood flow, increased vascularization and decreased resistance index after administering low-dose vs. ultra-low-dose MHT therapy that should be taken into account upon planning therapeutic regimen and its timeframe.